2006
DOI: 10.3327/jnst.43.255
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Dissolution of UO2 Pellet Containing Simulated Fission Products in Ammonium Carbonate Solution

Abstract: We have proposed a reprocessing process based on the dissolution of spent fuels in aqueous carbonate solution. In order to develop such a reprocessing process, anodic dissolution experiments were carried out by using a simulated spent fuel pellet in (NH 4) 2 CO 3 solution. The dissolution rate constant of the simulated fuel pellet at 323 K was estimated as 3:1Â10 À6 molÁcm À2 Ámin À1 , which is comparable to that in 5 molÁdm À3 HNO 3 solution containing 0.01 molÁ dm À3 HNO 2 at 323 K. The dissolution rate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The use of anodic dissolution of simulated spent nuclear fuel containing UO 2 and fission products in alkaline aqueous solution using sodium carbonate-sodium bicarbonate [15] and ammonium carbonate solutions [16] has been performed. In these studies, uranyl ions were produced anodically as stable carbonate complexes, and at the same time, simulated fission products were precipitated as hydroxo or carbonate compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of anodic dissolution of simulated spent nuclear fuel containing UO 2 and fission products in alkaline aqueous solution using sodium carbonate-sodium bicarbonate [15] and ammonium carbonate solutions [16] has been performed. In these studies, uranyl ions were produced anodically as stable carbonate complexes, and at the same time, simulated fission products were precipitated as hydroxo or carbonate compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the electrolytic solution revealed that most of the simulated fission products, i.e. alkaline earth and rare earth elements, are precipitated in high ratios [16]. The aim of this work was to investigate the extraction of Uranium from irradiated target waste residue plates for Mo-99 production using alkaline extraction technology.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, carbonate solutions containing H 2 O 2 , can be used to purify uranium oxides, UO 2 or U 3 O 8 , contaminated with metal impurities. Recently, several carbonate-based processes have been studied and suggested to treat uranium-bearing waste and scraps generated during uranium fuel fabrication, uranium sludge and spent nuclear fuel [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This could have a significant impact on the dissolution and migration behavior of actinides in geological repositories for nuclear waste disposal. , Additionally, uranium is selectively dissolved to form uranyl peroxocarbonate species with a high solubility, UO 2 (O 2 ) x (CO 3 ) y 2–2 x –2 y , in a carbonate solution containing hydrogen peroxide, H 2 O 2 . In contrast to the uranyl peroxocarbonate complex, most transition-metal ions have very low solubilities in such an alkaline carbonate solution and do not form metal peroxo complex ions. Uranium in the mixed solution of hydrogen peroxide and sodium carbonate can be precipitated as uranium peroxide when the solution is acidified to a pH of 2–3. On the basis of these chemical characteristics of uranium, several carbonate-based processes have been studied and suggested to treat uranium-bearing wastes, uranium scraps generated during uranium fuel fabrication, uranium sludge, and spent nuclear fuel. , For these reasons, actinide peroxide chemistry has recently attracted significant attention.…”
Section: Introductionmentioning
confidence: 99%